2011
DOI: 10.1038/ismej.2011.134
|View full text |Cite
|
Sign up to set email alerts
|

Disconnect of microbial structure and function: enzyme activities and bacterial communities in nascent stream corridors

Abstract: A fundamental issue in microbial and general ecology is the question to what extent environmental conditions dictate the structure of communities and the linkages with functional properties of ecosystems (that is, ecosystem function). We approached this question by taking advantage of environmental gradients established in soil and sediments of small stream corridors in a recently created, early successional catchment. Specifically, we determined spatial and temporal patterns of bacterial community structure a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

4
112
3

Year Published

2013
2013
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 150 publications
(119 citation statements)
references
References 54 publications
4
112
3
Order By: Relevance
“…), there were notable differences in fungal and bacterial community composition among the five successional stages. The observed disconnect between microbial community composition and metabolic activity (i.e., between community structure and function) parallels a previous field survey of sediment microbial communities (32). It suggests that microbial communities on decomposing litter are as effective at exploiting their substrate in streams simulating very early successional conditions (i.e., no litter or only wood small-reed litter present) as in streams receiving litter of higher quality and in greater amounts.…”
Section: Discussionsupporting
confidence: 67%
See 1 more Smart Citation
“…), there were notable differences in fungal and bacterial community composition among the five successional stages. The observed disconnect between microbial community composition and metabolic activity (i.e., between community structure and function) parallels a previous field survey of sediment microbial communities (32). It suggests that microbial communities on decomposing litter are as effective at exploiting their substrate in streams simulating very early successional conditions (i.e., no litter or only wood small-reed litter present) as in streams receiving litter of higher quality and in greater amounts.…”
Section: Discussionsupporting
confidence: 67%
“…Bacterial and fungal biomass. Bacterial abundance was determined by flow cytometry after detaching bacterial cells from leaves and sediments by treating the leaves and sediments with an ultrasonic probe three times for 20 s each time (31,32). Briefly, the detached bacterial cells were separated from other particles by collecting them on top of Histodenz solution (33), staining with SYBR green I, and counting on a CyFlow space flow cytometer system (Partec, Görlitz, Germany) equipped with a 200-mW solid-state laser (light emission at 488 nm) and volumetric counting hardware (34).…”
mentioning
confidence: 99%
“…Application of deep sequencing technologies to the study of microbial community structure and function has resulted in the observation that variability in microbial community composition does not necessarily reflect differences in the functional potential of that community (19,36,37). Here we tested this hypothesis using RNA sequencing to identify the transcriptionally active microbial community members and the function of the genes being transcribed.…”
Section: Discussionmentioning
confidence: 99%
“…Frossard et al (2012) investigated EF and BCC in a nascent stream corridor and found a pronounced uncoupling between community composition and ecosystem functioning, with EF being mainly driven by seasonality, whereas BCC showed no seasonal pattern. They concluded that bacterial communities have a high functional redundancy within these early successional landscapes.…”
Section: Discussionmentioning
confidence: 99%